Raising Students’ Awareness on Their Teaching Performance through Reflective Teaching - Yenni Rozimela (Universitas Negeri Padang, 2014)
This article presents a part of the results of a study conducted to explain the application of reflective teaching to improve the students’ pedagogy competence in teaching English. The research was begun last February (2014), and will end by the end of this year (2014). The result described here is the students’ focus of attention in their reflective teaching. The study was conducted with 15 students taking Micro Teaching unit course. Prior to the commencement of the study, the students were informed about the concept and the importance of reflective teaching. Example of doing reflective teaching was also given. The students taught English to their peers in a range of selected texts prescribed in the junior and senior high school curricula. Every student taught for times (20- 40 minutes for each). After teaching presentation, the students were required to articulate their opinions about their teaching, and write their reflection in a journal. The reflection may consist of several teaching aspects such as instructional material, teaching techniques or strategies, and language use. The result of this study shows that the most frequent aspects that became the focus of concern of the students were teaching techniques and materials. Sometimes they also reflected upon the use of teaching media and classroom management. Unfortunately, they hardly reflected on their language use. The result of this study is expected to give a useful insight to prepare students for their professional development as teachers.